INQUIRY-BASED LEARNING WORKSHEET TO IMPROVE UNDERSTANDING SCIENCE CONCEPTS IN ELEMENTARY SCHOOL - Astri Sutisnawati; Din Azwar Uswatun (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2018)
This research was aim to find out the effect of Inquiry-Based Learning Worksheet to improve mastering science concepts in Elementary School. This research used quasi-experimental as a research method with a single group pretest-posttest research design. The observation was made twice in this research design that are done before the treatment and after the treatment. The observation that took before the treatment (O) is called pretest (initial test) and the observation that took after the observation is called post-test (final test). The difference or gai between initial test and final test are assumed to be the influence of the treatment. The result of this study suggest that inquiry learning based worksheet has an effect to improve the understading of science concepts with 0.68 N-Gain (Medium Category). This shows that student’s inquiry learning based worksheet can be used as teaching materials to improve their understanding of science concept.